A case of erythrodermic psoriasis successfully treated with guselkumab. Issue 2 (6th February 2020) - Megna, Matteo; Ruggiero, Angelo; Camela, Elisa; Fabbrocini, Gabriella; Marasca, Claudio
Abstract: Erythrodermic psoriasis (EP) is the most severe form of psoriasis, resulting in significant morbidity and mortality. EP treatment with biologics is not well ruled by international guidelines, so most biological drugs are used basing on case reports or small case series. Guselkumab, a fully human anti‐interleukin (IL)‐23 monoclonal antibody, is approved for moderate to severe plaque psoriasis while its use in EP is off label. To date, no case reports on Caucasian patients have been described in the literature. We report the case of 38‐year‐old Caucasian male with EP successfully treated with guselkumab, reaching PASI 100 after 20 weeks of therapy and still maintaining this response at Week 48. Our case report suggests guselkumab as an efficacious and well‐tolerated treatment in EP, presenting a long‐term efficacy in the prevention of recurrences. Further studies are warrant to confirm our data, with controlled trials specifically dedicated to EP being strictly needed in order to verify the role and efficacy of anti‐IL23 in EP.